Australian Pharmacists' Perceptions and Practices in Travel Health - Ian M. Heslop; Richard Speare; Michelle Bellingan; Beverley D. Glass (MDPI AG, 2018)
Worldwide, pharmacists are playing an increasing role in travel health, although legislation and funding can dictate the nature of this role, which varies from country to country. The aim of this study was to explore the current and potential future practices in travel health for pharmacists in Australia, as well as the perceived barriers, including training needs, for the provision of services. A survey was developed and participation was sought from a representative sample of Australian pharmacists, with descriptive statistics calculated to summarise the frequency of responses. A total of 255 participants, predominantly female (69%), below 50 years (75%) and registered less than 30 years completed the survey. Although over two-thirds (68%) provided travel-related advice in their current practice, the frequency of advice provision was low (less than 2 travellers per week) and limited to responding to travellers questions. Although Australian pharmacists are currently unable to administer travel vaccines and prescription only medications without prescription, they still consider travel health to be an appropriate role and that their clients would seek travel health advice from pharmacies if offered. Currently, key roles for Australian pharmacists are advising travellers who do not seek advice from other practitioners, reinforcing the advice of other health practitioners and referring travellers needing vaccinations and antimalarials. In order to expand these services, the barriers of workload, time, staffing and the need for training in travel health need to be addressed. In summary, the travel health services provided by pharmacies in Australia still have a way to go before they match the services offered by pharmacies in some other countries, however Australian pharmacist are keen to further develop their role in this area.